Biostatistics for the biological and health sciences - Triola, Marc M.; Triola, Mario F.; Roy, Jason (Jason Allen) (Pearson, 2024)
"Popular textbook that examines the relationship between statistics and our world through extensive use of a wide variety of real world applications that bring life to statistical theory and methods"--